Empirical Prints - Verfremdung & Fabrications - Ostrowski, Kasper (STS Encounters, 2018)
From the introduction: ‘Empirical Prints’ was initiated as an open-ended experimental project. The craft based research project served no clear-cut purpose and had no unequivocal resolutions in mind. However, it was devised with a multitude of sensitivities. As a non-conventional printmaker and STS scholar, I aspired to introduce and experiment with the practice of printmaking in an academic setting. Furthermore, I was intrigued by STS’s long standings concern with materiality and especially the focus on the relational quality of materiality (E.g.: Bennett 2010; Coole and Frost 2010; Weibel and Latour 2005). Lastly the project grew out of an interest for ways of re-enchanting otherwise forgotten and “invisible objects”; litter, garbage, mundane items etc. Inspired by both STS and theatre theorist & play writer Bertolt Brecht, I aimed at making the natural look surprising.